Revealing major macroeconomic growth factors for an emerging economy: evidence from half-century of economic resilience - Mehedi Hasan; Md. Obidul Haque; Md. Saddam Hossain; Md. Ahsan Habib; Mohammad Bin Amin; Md. Atikur Rahaman; Judit Oláh (Discover Sustainability)
Abstract Bangladesh’s economic transformation over the past 50 years, from one of the world’s poorest nations to an emerging middle-income economy, provides a compelling context for analysing macroeconomic growth factors. This study aims to identify key determinants of Bangladesh’s economic growth, examining how variables such as foreign direct investment (FDI), government expenditure, trade openness, inflation, exchange rates, and official aid have influenced growth over the long and short term. Using an autoregressive distributed lag (ARDL) bounds testing approach, the study leverages 50 years of time-series data to explore the dynamic relationships between these macroeconomic factors and economic growth. The findings reveal that FDI, government consumption, and trade openness significantly boost economic growth, while inflation and exchange rate appreciation exert negative effects. Diagnostic tests confirm the model’s robustness, with stability tests indicating consistent parameter reliability across the sample period. However, this research is limited by the use of secondary data and potential measurement biases, suggesting the need for primary data in future studies. The study holds practical implications for policymakers, offering evidence-based recommendations to attract sustained FDI, manage inflation and exchange rate stability, and optimise aid utilisation. By comprehensively examining Bangladesh’s macroeconomic landscape, this research adds original insights into the resilience factors underpinning emerging economies, contributing valuable guidance for policy initiatives to foster sustainable growth.